2016
DOI: 10.1016/j.neuroscience.2015.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Tauroursodeoxycholic acid prevents hearing loss and hair cell death in Cdh23 mice

Abstract: Sensorineural hearing loss has long been the subject of experimental and clinical research for many years. The recently identified novel mutation of the Cdh23 gene, Cdh23erl/erl, was proven to be a mouse model of human autosomal recessive nonsyndromic deafness (DFNB12). Tauroursodeoxycholic acid (TUDCA), a taurine-conjugated bile acid, has been used in experimental research and clinical applications related to liver disease, diabetes, neurodegenerative diseases, and other diseases associated with apoptosis. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Erl mice have the Cdh23 erl/erl mutation which confers non-syndromic autosomal recessive deafness by altering the CDH23 protein in the upper part of the tip-link in HCs. These mice were a novel tool in assessing otoprotective drugs because of the time frame from the initiation of HC death to when complete deafness occurs (Hu et al, 2016 ). The experiments showed that the TUDCA-treated mice had significantly preserved as hearing determined by auditory brainstem response (ABR) and distortion product otoacoustic emissions (DPOAE) tests possibly due to the downregulation of caspase-3 and caspase-9 which was determined using western blot studies (Hu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erl mice have the Cdh23 erl/erl mutation which confers non-syndromic autosomal recessive deafness by altering the CDH23 protein in the upper part of the tip-link in HCs. These mice were a novel tool in assessing otoprotective drugs because of the time frame from the initiation of HC death to when complete deafness occurs (Hu et al, 2016 ). The experiments showed that the TUDCA-treated mice had significantly preserved as hearing determined by auditory brainstem response (ABR) and distortion product otoacoustic emissions (DPOAE) tests possibly due to the downregulation of caspase-3 and caspase-9 which was determined using western blot studies (Hu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…These mice were a novel tool in assessing otoprotective drugs because of the time frame from the initiation of HC death to when complete deafness occurs (Hu et al, 2016 ). The experiments showed that the TUDCA-treated mice had significantly preserved as hearing determined by auditory brainstem response (ABR) and distortion product otoacoustic emissions (DPOAE) tests possibly due to the downregulation of caspase-3 and caspase-9 which was determined using western blot studies (Hu et al, 2016 ). TUDCA’s efficacy was also tested in gentamicin induced ototoxicity using both mouse primary OC explant cultures and an OC cell line, HEI-OC1.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that TUDCA alleviates ER stress by enhancing the capacity of folding enzymes in the ER or by regulating Ca 2+ homeostasis in the ER [Vega et al, 2016]. In addition, TUDCA ameliorates numerous types of ER stress-related diseases [Hetz et al, 2013], including various types of hearing loss [Hu et al, 2016b;Oishi et al, 2015]. In our study, we not only observed the induction of ER stress in cochlear cells following cisplatin treatment but also confirmed the alleviating effect of the classical proteostasis promoter TUDCA on cisplatin-induced ototoxicity ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…OHC was counted as present if V-shape of hair bundles was intact. Counts of OHC in three continuous views for each turn of a cochlea were recorded and analysed [ 17 ].…”
Section: Methodsmentioning
confidence: 99%